Your Wait Time From This Point Will Be . . .: Practices for Designing Amusement Park Queues. (April 2013) - Ledbetter, Jonathan L.; Mohamed-Ameen, Amira; Oglesby, James M.; Boyce, Michael W.
Amusement park developers have begun designing queue systems to make the wait for service less cumbersome for guests. Maister introduced a theoretical framework with eight guidelines for improving customer satisfaction and minimizing the perception of wait duration. These guide- lines were designed to be generalizable to a wide range of settings but do not fully take into account the unique characteristics of theme park queues. The following proposed guidelines offer a taxonomy for reducing the negative impact of subjective perception of time and provide a specific framework for designing these queued environments in an amusement park setting.